2022
DOI: 10.3390/app122413046
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characteristics of Pre-Peak Unloading Damage and Mechanisms of Reloading Failure in Red Sandstone

Abstract: The mining of deep coal resources occurs in a high-stress geological environment as well as an engineering environment of rock excavation and unloading. Research on the re-bearing capacity characteristics and damage mechanism of rock masses damaged by peak front unloading is critical in revealing the destabilization and rupture law of deep rock bodies. The triaxial pre-peak unloading point was controlled to prepare damaged sandstone specimens, and the RMT-150C rock mechanics test loading system and the AEwin U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The mechanical properties of rock (masses) will be different depending on the stress environment. Scholars have conducted indoor mechanical tests on various types of rocks (masses) under complex stress environments and these can be roughly divided into loading mechanical, unloading mechanical [2], cyclic loading and unloading mechanical [3][4][5][6][7], and damage reloading mechanical tests [8][9][10]. Previous studies [11][12][13] conducted indoor loading tests and studied the stress-strain curves, deformation, and failure characteristics of sandstone and conglomerate specimens under various confining pressures.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of rock (masses) will be different depending on the stress environment. Scholars have conducted indoor mechanical tests on various types of rocks (masses) under complex stress environments and these can be roughly divided into loading mechanical, unloading mechanical [2], cyclic loading and unloading mechanical [3][4][5][6][7], and damage reloading mechanical tests [8][9][10]. Previous studies [11][12][13] conducted indoor loading tests and studied the stress-strain curves, deformation, and failure characteristics of sandstone and conglomerate specimens under various confining pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Krzysztof et al [20] found through experiments and numerical simulations that a reasonable support method can effectively improve the stability of the fault area and the rock surrounding the roadway. Zhu et al [21,22] studied the mechanical characteristics of fractured surrounding rock in damaged tunnels and analyzed the mechanical deformation and failure characteristics of fractured surrounding rock through rock mechanics experiments. Yu et al [23,24] carried out three-dimensional geological modeling of a quarry containing close-range double faults based on the site, and through similar simulation experiments and three-dimensional numerical simulation analysis, they derived the form of mutual transformation of the energy and stress of the two faults in the whole mining process of the quarry, the overall joint control mechanism of the faults on the regional peripheral rock structure, and the law of the mutual influence of the faults, and, moreover, they gave a map of the joint action of the two faults in the whole mining process.…”
Section: Introductionmentioning
confidence: 99%